Assessing Distributed Leadership Practice in Korea: An Exploratory Study on Scale Development - Joo, Young Hyeo; Kim, Juhu (KEDI Journal of Educational Policy, 2024)
This study aimed to develop empirically a distributed leadership practice scale (DLPS) that can be applied to Korean secondary schools. As an exploratory study, scale development comprised conducting theoretical analyses to extract measurable constructs; 29 items were developed for the validation of the scale. The DLPS was administered to 489 secondary school teachers; the reliability and validity of the scale were examined by using Cronbach’s alpha and then factor analysis. The reliability was 0.96. The results of factor analysis revealed four subconstructs: educational quality improvement activity, principal leadership, teacher participation, and collegial culture, on which our suggestions for further research were based. The DLPS is critical to diagnosing the current school leadership practice, formulating a plan for school improvement, and educational policymaking and implementation.
Keywords: distributed leadership; educational artifact; principal leadership; school culture; school structure